Perineural low dexamethasone dose as adjuvant in supraclavicular brachial plexus block for arteriovenous fistula creation in end stage renal disease: a randomized controlled trial - Pande, Aparna; Sen, Indu Mohini; Gupta, Aakriti; Gupta, Ankur; Sharma, Ashish (Brazilian journal of anesthesiology (Elsevier), 2023)
Dexamethasone as adjunct to local anesthetic solution improves the quality of brachial plexus block (BPB). However, evidence for its efficacy at low doses (< 4 mg) is lacking. This study was designed to evaluate the duration of analgesia attained with low dose dexamethasone as adjuvant to local anesthetic for creation of arteriovenous fistula (AVF) under BPB. Sixty-six patients scheduled for AVF creation were randomly allocated to receive either saline (control) or 2 mg dexamethasone, together with 0.5% ropivacaine and 0.2% lignocaine. The primary outcome was duration of analgesia, defined as time from performing the block to the first analgesic request. The secondary outcomes were time from injection to complete sensory block, time from injection to complete motor block, duration of motor block, postoperative analgesic consumption, and fistula patency at three months. All the blocks were effective. In the group that received dexamethasone, the time to first analgesic request was significantly delayed (432 ± 43.8 minutes vs. 386.4 ± 40.2 minutes; p < 0.01). The onset of sensory and motor blockade occurred faster in dexamethasone group and overall analgesic consumption was also reduced. However, dexamethasone addition did not prolong the duration of motor block. There was no statistically significant difference in the patency of fistulas between the two groups at three months. (p = 0.34). Addition of low-dose perineural dexamethasone to local anesthetic solution significantly prolonged the duration of analgesia. Further trials are warranted to compare the adverse effects between dexamethasone doses of 4 mg and lower.